Pembuatan Kulit Pie Berbahan Dasar Tepung Porang - Ester Grace Enita; Niken Purwidiani; Ila Huda Puspita Dewi; Mauren Gita Miranti (Pusat Riset dan Inovasi Nasional, 2024)
Pie crust made from porang flour is an innovation that utilizes the results of cultivating porang tubers. This research aims to determine: 1) the best sensory test quality of pie crust made from porang flour; 2) nutritional content, namely water, fat, protein, carbohydrate, ash and fiber content; 3) selling price for pie crust made from porang flour per piece weighing 30 gr. The research method used was experimentation by carrying out 3 different treatments to determine the best sensory test. The research method used in this research is experimentation. The data collection technique is through sensory quality testing using instruments with 30 panelists. The data that has been collected is then analyzed using SPSS version 27 single anova test (one way anova). The research results show that; 1) the formula used to make pie crust is made from porang flour using 60% porang flour and 40% wheat flour, with the formulation 210-grams of porang flour, 140-grams of wheat flour, 25-grams of refined sugar, 280-grams of margarine, 1 ½ tsp salt, 85-ml ice water; 2) laboratory test results for the nutritional content of pie crust made from porang flour, namely water content 7.11%, fat 2.96%, protein 6.11%, carbohydrates 67.90%, ash 0.91%, fiber 3.62% ; and 3) The selling price of pie crust made from porang flour per piece weighing 30 grams.